1995
DOI: 10.1007/bf00002591
|View full text |Cite
|
Sign up to set email alerts
|

Changes in heated and autoclaved forest soils of S.E. Australia. I. Carbon and nitrogen

Abstract: Abstract. The effect of heating and autoclaving on extractable nitrogen, N mineralisation and C metabolism was studied by heating five forest soils in the laboratory, simulating the range of effects of heat due to bushfire.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 55 publications
4
44
1
Order By: Relevance
“…However, when a large amount of the slashed biomass was burned as in the case of the T -100 plot, soil microbes may experience serious damage. Serrasolsas and Khanna (1995) observed a rapid recovery of microbial biomass after burning at less than 120T but no response at 250T in their laboratory burning experiments. The content of NH 4 -N decreased and that of N0 3 -N increased (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, when a large amount of the slashed biomass was burned as in the case of the T -100 plot, soil microbes may experience serious damage. Serrasolsas and Khanna (1995) observed a rapid recovery of microbial biomass after burning at less than 120T but no response at 250T in their laboratory burning experiments. The content of NH 4 -N decreased and that of N0 3 -N increased (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…1, in which the difference in the increase of the NH 4 -N content by burning was relatively small among the soils from T -0 to T -50. Serrasolsas and Khanna (1995) described the reasons for the increase in the amounts of easily extractable C and N as follows, 1) lysis of microbial cells, 2) increase in the solubility of both non-microbial organic N and inorganic forms of N, and 3) partial ashing of organically bound nutrients. Russell et al (1974) concluded that flush of NH 4 -N during soil heating at 100 to 230'C could be ascribed to the thermal decomposition of organic matter or killed microbes, mainly secondary amide groups and amino acids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, fumigation methods (Ladd and Amato 1988) as well as autoclaving (Serrasolsas and Khanna 1995) were shown to increase potentially bioavailable C and N by releasing water-soluble compounds. Also, the potential release of soil components in water may affect soluble compounds as well as colloids involved in soil aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the potential release of soil components in water may affect soluble compounds as well as colloids involved in soil aggregation. Release of soil organic components may supply substrates for microbial growth, although contrasting results showed either immediate use by microorganisms (Serrasolsas and Khanna 1995) or use after a lag phase (Leinweber et al 1995). Moreover, the water-extractable organic matter (WEOM) quality may differ among soil types and managements (Chantigny 2003).…”
Section: Introductionmentioning
confidence: 99%